SURGICAL TREATMENT METHODS OF ACUTE LOWER LIMB ARTERIAL THROMBOSIS ON PATIENTS AFTER CORONAVIRUS INFECTION - Uktamkhon Asrarov; Jakhongir K. Matmuradov (Central Asian Journal of Medicine, 2023)
This article reflects the result of different types of surgical interventions on patients with lower limb arterial thromboses, who had had coronavirus infection. 43 patients were divided into 2 groups: the 1st group underwent to thrombectomies, whereas 2nd group – catheter thrombolysis and thrombaspiration. The results demonstrates applying of catheter thrombolysis instead of thrombectomy significantly decreases frequency of complications, rethromboses and mortality.